Minat Siswa Kelas XI Dalam Mengikuti Kegiatan Ekstrakurikuler Olahraga Di SMA Negeri 22 Palembang - Ridki Fahrul Rahmatulloh; Rury Rizhardi; Endie Riyoko (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The type of research used in this research is descriptive qualitative research. In this research, descriptive qualitative research was used to determine the interest of class XI students in participating in extracurricular sports activities at SMA Negeri 22 Palembang. The population in this study was 30 class XI students at SMA Negeri 22 Palembang. The data collection technique uses total sampling. The sample used in this research was 30 respondents with a total of 30 statement items. The data collection procedure uses a questionnaire using Google Forms and data analysis techniques for this research use simple descriptive statistics in analyzing student interest. The research results show that class XI students' interest in participating in extracurricular sports activities received a response with a percentage of 83% in the good category. Seeing the response results which reached more than 50%, it means that class XI students prefer to take part in extracurricular sports activities.